2022
DOI: 10.1002/ps.6873
|View full text |Cite
|
Sign up to set email alerts
|

Time‐series analysis of population dynamics of the common cutworm,Spodoptera litura(Lepidoptera: Noctuidae), using anARIMAXmodel

Abstract: BACKGROUND Developing a model that adequately explains pest population dynamics based on weather‐related parameters is fundamentally important for proper pest management. Autocorrelation with past occurrences should be considered when modeling the relationship between the time series of pest occurrence data and meteorological factors; however, few attempts have been made to model these factors simultaneously. In this study, we constructed an autoregressive integrated moving average with exogenous variables (AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…For Asian corn borer, cotton bollworm, and peach borer. Temperature and relative humidity are extensively used key climatic factors in lepidopteran pest outbreak prediction models, including cotton bollworm and corn borer [27]. Sexual attractants and frequencyvibration insect-killing lamps were used to monitor the insect in sweet corn fields, which can reduce systemic error because previous research has demonstrated that male Conogethes punctiferalis sensitivity to sexual attractants greatly changed after mating [28].…”
Section: Discussionmentioning
confidence: 99%
“…For Asian corn borer, cotton bollworm, and peach borer. Temperature and relative humidity are extensively used key climatic factors in lepidopteran pest outbreak prediction models, including cotton bollworm and corn borer [27]. Sexual attractants and frequencyvibration insect-killing lamps were used to monitor the insect in sweet corn fields, which can reduce systemic error because previous research has demonstrated that male Conogethes punctiferalis sensitivity to sexual attractants greatly changed after mating [28].…”
Section: Discussionmentioning
confidence: 99%
“…The other parameters are the same as described in Eq. ( 1 ) above 19 , 20 . In this study, SARIMAX models were developed based on spearman’s results, and the optimal model was selected by comparing the values of stationary , , MAPE, and BIC for different models.…”
Section: Methodsmentioning
confidence: 99%
“…This study employed the variance inflation factor (VIF) statistic. If the VIF is greater than five or, sometimes, ten, serious multicollinearity among the exogenous variables in the model can be detected ( Ihueze & Onwurah, 2018 ; Kawakita & Takahashi, 2022 ). In Table 2 , all of these values are less than five, indicating that the degree of multicollinearity between the explanatory variables is insignificant.…”
Section: Methodsmentioning
confidence: 99%